Analyzing determinants of economic growth on agricultural sector in Indonesia - Bagus Wiranatakusuma Dimas; Fairuztama Rafif; Aprizal Anggi (E3S Web of Conferences)
Despite the crucial role of agriculture in safeguarding Indonesia’s economy, some attention has given to the nation’s agricultural development, banking dynamics, and macroeconomic landscape pre- and post-COVID-19 era. This study employs quarterly data spanning from 2010 to 2021, using multiple Ordinary Least Squares (OLS) regression techniques to analyse various variables. Key variables examined include the growth of agriculture’s GDP shares over total GDP (GGDPRGDPT), agriculture’s financing and total time deposits in Islamic banks (GFinPDT), Islamic banks’ margin in agriculture (MARGIN), agriculture’s financing and GDP in agriculture (GCPGDPP), inflation, and food prices. The findings underscore the imperative for Indonesia’s agriculture sector to embark on a transformative journey toward enhanced productivity. Moreover, sustained support from the banking sector is considered essential for fostering financial deepening, causing a higher allocation of deposited funds towards agricultural financing. Amidst pandemics and crises, the resilience of Indonesia’s agriculture sector is underscored by the indispensability of its products. However, collaborative efforts between farmers and financial institutions are called for, alongside proactive measures by banks to channel deposited funds into agricultural financing instruments. The sustainable growth of Indonesia’s agricultural sector hinges upon robust macroeconomic conditions, effective management practices, and unwavering support from the banking sector.